5.4.3 Problems 201 to 300

Table 5.419: Second ODE homogeneous ODE

#

ODE

Mathematica

Maple

1295

\[ {}t^{2} y^{\prime \prime }+3 t y^{\prime }+\frac {5 y}{4} = 0 \]

1296

\[ {}t^{2} y^{\prime \prime }-4 t y^{\prime }-6 y = 0 \]

1297

\[ {}t^{2} y^{\prime \prime }-4 t y^{\prime }+6 y = 0 \]

1298

\[ {}t^{2} y^{\prime \prime }-t y^{\prime }+5 y = 0 \]

1299

\[ {}t^{2} y^{\prime \prime }+3 t y^{\prime }-3 y = 0 \]

1300

\[ {}t^{2} y^{\prime \prime }+7 t y^{\prime }+10 y = 0 \]

1301

\[ {}y^{\prime \prime }+t y^{\prime }+{\mathrm e}^{-t^{2}} y = 0 \]

1302

\[ {}t y^{\prime \prime }+\left (t^{2}-1\right ) y^{\prime }+t^{3} y = 0 \]

1303

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 0 \]

1304

\[ {}9 y^{\prime \prime }+6 y^{\prime }+y = 0 \]

1305

\[ {}4 y^{\prime \prime }-4 y^{\prime }-3 y = 0 \]

1306

\[ {}4 y^{\prime \prime }+12 y^{\prime }+9 y = 0 \]

1307

\[ {}y^{\prime \prime }-2 y^{\prime }+10 y = 0 \]

1308

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

1309

\[ {}4 y^{\prime \prime }+17 y^{\prime }+4 y = 0 \]

1310

\[ {}16 y^{\prime \prime }+24 y^{\prime }+9 y = 0 \]

1311

\[ {}25 y^{\prime \prime }-20 y^{\prime }+4 y = 0 \]

1312

\[ {}2 y^{\prime \prime }+2 y^{\prime }+y = 0 \]

1313

\[ {}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0 \]

1314

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

1315

\[ {}9 y^{\prime \prime }+6 y^{\prime }+82 y = 0 \]

1316

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 0 \]

1317

\[ {}4 y^{\prime \prime }+12 y^{\prime }+9 y = 0 \]

1318

\[ {}y^{\prime \prime }-y^{\prime }+\frac {y}{4} = 0 \]

1319

\[ {}t^{2} y^{\prime \prime }-4 t y^{\prime }+6 y = 0 \]

1320

\[ {}t^{2} y^{\prime \prime }+2 t y^{\prime }-2 y = 0 \]

1321

\[ {}t^{2} y^{\prime \prime }+3 t y^{\prime }+y = 0 \]

1322

\[ {}t^{2} y^{\prime \prime }-t \left (2+t \right ) y^{\prime }+\left (2+t \right ) y = 0 \]

1323

\[ {}x y^{\prime \prime }-y^{\prime }+4 x^{3} y = 0 \]

1324

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

1325

\[ {}x^{2} y^{\prime \prime }-\left (x -\frac {3}{16}\right ) y = 0 \]

1326

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

1327

\[ {}t^{2} y^{\prime \prime }-3 t y^{\prime }+4 y = 0 \]

1328

\[ {}t^{2} y^{\prime \prime }+2 t y^{\prime }+\frac {y}{4} = 0 \]

1329

\[ {}2 t^{2} y^{\prime \prime }-5 t y^{\prime }+5 y = 0 \]

1330

\[ {}t^{2} y^{\prime \prime }+3 t y^{\prime }+y = 0 \]

1331

\[ {}4 t^{2} y^{\prime \prime }-8 t y^{\prime }+9 y = 0 \]

1332

\[ {}t^{2} y^{\prime \prime }+5 t y^{\prime }+13 y = 0 \]

1355

\[ {}u^{\prime \prime }+2 u = 0 \]

1356

\[ {}u^{\prime \prime }+\frac {u^{\prime }}{4}+2 u = 0 \]

1483

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 0 \]

1484

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 0 \]

1485

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 0 \]

1486

\[ {}y^{\prime \prime }-2 y^{\prime }+4 y = 0 \]

1487

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 0 \]

1737

\[ {}y^{\prime \prime }-7 y^{\prime }+10 y = 0 \]

1738

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 0 \]

1739

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 0 \]

1740

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 0 \]

1741

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 0 \]

1742

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }+4 x y^{\prime }+2 y = 0 \]

1743

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 0 \]

1744

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

1745

\[ {}y^{\prime \prime }-2 a y^{\prime }+a^{2} y = 0 \]

1746

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-y = 0 \]

1747

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+y = 0 \]

1748

\[ {}x^{2} y^{\prime \prime }-\left (2 a -1\right ) x y^{\prime }+a^{2} y = 0 \]

1749

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (-16 x^{2}+3\right ) y = 0 \]

1750

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

1751

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

1752

\[ {}4 x^{2} \sin \left (x \right ) y^{\prime \prime }-4 x \left (\sin \left (x \right )+x \cos \left (x \right )\right ) y^{\prime }+\left (2 x \cos \left (x \right )+3 \sin \left (x \right )\right ) y = 0 \]

1753

\[ {}\left (3 x -1\right ) y^{\prime \prime }-\left (3 x +2\right ) y^{\prime }+\left (6 x -8\right ) y = 0 \]

1754

\[ {}\left (x^{2}-4\right ) y^{\prime \prime }+4 x y^{\prime }+2 y = 0 \]

1755

\[ {}\left (2 x +1\right ) y^{\prime \prime }-2 \left (2 x^{2}-1\right ) y^{\prime }-4 \left (1+x \right ) y = 0 \]

1756

\[ {}\left (x^{2}-2 x \right ) y^{\prime \prime }+\left (-x^{2}+2\right ) y^{\prime }+\left (2 x -2\right ) y = 0 \]

1774

\[ {}x y^{\prime \prime }+\left (-2 x +2\right ) y^{\prime }+\left (x -2\right ) y = 0 \]

1775

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

1776

\[ {}x^{2} \ln \left (x \right )^{2} y^{\prime \prime }-2 x \ln \left (x \right ) y^{\prime }+\left (2+\ln \left (x \right )\right ) y = 0 \]

1777

\[ {}4 x y^{\prime \prime }+2 y^{\prime }+y = 0 \]

1778

\[ {}x y^{\prime \prime }-\left (2+2 x \right ) y^{\prime }+\left (x +2\right ) y = 0 \]

1779

\[ {}x^{2} y^{\prime \prime }-\left (2 a -1\right ) x y^{\prime }+a^{2} y = 0 \]

1780

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

1781

\[ {}x y^{\prime \prime }-\left (4 x +1\right ) y^{\prime }+\left (4 x +2\right ) y = 0 \]

1782

\[ {}4 x^{2} \sin \left (x \right ) y^{\prime \prime }-4 x \left (\sin \left (x \right )+x \cos \left (x \right )\right ) y^{\prime }+\left (2 x \cos \left (x \right )+3 \sin \left (x \right )\right ) y = 0 \]

1783

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (-16 x^{2}+3\right ) y = 0 \]

1784

\[ {}\left (2 x +1\right ) x y^{\prime \prime }-2 \left (2 x^{2}-1\right ) y^{\prime }-4 \left (1+x \right ) y = 0 \]

1785

\[ {}\left (x^{2}-2 x \right ) y^{\prime \prime }+\left (-x^{2}+2\right ) y^{\prime }+\left (2 x -2\right ) y = 0 \]

1786

\[ {}x y^{\prime \prime }-\left (4 x +1\right ) y^{\prime }+\left (4 x +2\right ) y = 0 \]

1788

\[ {}\left (3 x -1\right ) y^{\prime \prime }-\left (3 x +2\right ) y^{\prime }-\left (6 x -8\right ) y = 0 \]

2362

\[ {}2 t^{2} y^{\prime \prime }+3 t y^{\prime }-y = 0 \]

2363

\[ {}y^{\prime \prime }+t y^{\prime }+y = 0 \]

2364

\[ {}y^{\prime \prime }-y = 0 \]

2365

\[ {}6 y^{\prime \prime }-7 y^{\prime }+y = 0 \]

2366

\[ {}y^{\prime \prime }-3 y^{\prime }+y = 0 \]

2367

\[ {}3 y^{\prime \prime }+6 y^{\prime }+3 y = 0 \]

2368

\[ {}y^{\prime \prime }-3 y^{\prime }-4 y = 0 \]

2369

\[ {}2 y^{\prime \prime }+y^{\prime }-10 y = 0 \]

2370

\[ {}5 y^{\prime \prime }+5 y^{\prime }-y = 0 \]

2371

\[ {}y^{\prime \prime }-6 y^{\prime }+y = 0 \]

2372

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 0 \]

2373

\[ {}t^{2} y^{\prime \prime }+\alpha t y^{\prime }+\beta y = 0 \]

2374

\[ {}t^{2} y^{\prime \prime }+5 t y^{\prime }-5 y = 0 \]

2375

\[ {}t^{2} y^{\prime \prime }-t y^{\prime }-2 y = 0 \]

2376

\[ {}y^{\prime \prime }+2 y^{\prime }+4 y = 0 \]

2377

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

2378

\[ {}2 y^{\prime \prime }+3 y^{\prime }+4 y = 0 \]

2379

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

2380

\[ {}4 y^{\prime \prime }-y^{\prime }+y = 0 \]

2381

\[ {}y^{\prime \prime }+y^{\prime }+2 y = 0 \]

2382

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 0 \]